Village Endline Survey: Site Analysis Report for Nyando - Katuk Odeyo, Kenya (KE0101) - Chelangat, Risper; Okoth, Kevin; Setey, Rita; Musuya, David; Ochieng, Brian (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This study used community-level focus group discussions in the seven villages of the Nyando climate-smart villages (CSVs) in Kenya. The discussions were complemented with satellite images from mixed sources and GIS-based analytics to monitor the changes in land use and land cover over the past 10 years (2011-2021). There is solid evidence, from discrete ground evidence as well as the processed satellite imagery covering the region, that the area has improved significantly in farm and land management practices – an outcome partly attributable to interventions by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and partners, including Community-Based and Development Organizations working in the area. From the Normalized Difference Vegetation Index (NDVI) analysis, the formerly open ground and barren land in the northern section has improved in vegetative cover and infrastructure development over the decade. Similarly, the southern part has remarkably grown green over the same period, referred to here as the haven of exemplary green growth. The study further confirms decline in farm sizes due to rapidly rising population; increase in gullies in some villages or widening of pre-existing ones; improvements in social infrastructures such as schools, health facilities, electricity and roads; expanding economic opportunities as reflected by growth in local markets; and increasing access to information, especially agro-advisory services. Overall, livelihoods seem to have improved in Nyando, as evident in improved human settlements. The communities have a vision of an improved village with more and better schools and health facilities, increased forest cover, well managed and conserved wetlands, springs, and rivers increased water harvesting for domestic use and irrigation, improved road and market infrastructure, improved access to agricultural extension services, quality inputs and irrigation water, and better soil and water management.